Migrações de jovens rurais e formação superior: o caso da Universidade Federal da Fronteira Sul Campus Realeza – PR - Lamb, Talita Lúcia (2017)
The dissertation focuses on the migration of rural youths who attend higher education in the interior of the State of Paraná. The research object is rural young people who attend higher education at the Federal University of Southern Frontier (UFFS) Campus Realeza PR. The objective is to identify the possible relations existing between the social representations of these rural youngsters about migratory processes and the higher education in that university. It is considered that the fact of young people stays or leaves the rural environment is related (although not exclusively) to the way in which he represents this decision. In this sense, we believe in the possibility of identifying trends in migratory processes of rural young people based on the social representations of the subjects. In order to achieve the field research proposal, with data collection for the questionnaire technique, which were applied to the rural young people who attend the initial and final years of UFFS undergraduate courses, with a view to comparing the variables through of the time.